Adhesion of Pseudomonas aeruginosa to respiratory mucins and expression of mucin-binding proteins are increased by limiting iron during growth. - Scharfman, A (1996)
The attachment of Pseudomonas aeruginosa to human respiratory mucus represents an important step in the development of lung infection, especially in cystic fibrosis. Local factors in the respiratory tract, such as osmolarity or iron concentration, might influence this colonization. In the present work, we have observed that overall levels of adhesion of two nonmucoid, nonpiliated strains of P. aeruginosa, 1244-NP and PAK-NP, to human airway mucins were higher when these strains were grown in a minimal medium of low osmolarity (M9) than when they were grown in a rich medium of higher osmolarity (tryptic soy broth [TSB]). However, increasing the NaCl concentration of M9 to increase the osmolarity did not modify the level of binding. In order to find out whether these differences were due to variations in nutrients, the influence of iron concentration was investigated: the levels of binding of the two strains increased after TSB was depleted of iron and decreased after iron was added to M9. Since the outer membranes from the two strains have been shown to contain proteins reacting with human bronchial mucins, we compared the mucin-binding proteins expressed by the two strains grown in different media. When the nonpiliated strains 1244-NP and PAK-NP were grown in the different media, previously observed mucin-binding bands were detected in the 42- to 48-kDa range but additional mucin-binding bands in the 77- to 85-kDa range were detected when these strains were grown in M9 or iron-deprived TSB. These results demonstrate that the adhesion of P. aeruginosa and the expression of mucin-binding proteins in the outer membranes of nonpiliated P. aeruginosa are affected by the iron content of the medium in which the bacteria are grown and not by the osmolarity.